Effects of Stereotype-Focused Imagined Contact on Young Adults' Intentions for Intergenerational Interaction. (19th August 2022) - Fowler, Craig; Gasiorek, Jessica
Abstract: Objectives: Face-to-face intergenerational contact is associated with more positive attitudes toward older adults. However, such contact can be difficult to achieve, and poor contact experiences can have negative consequences for intergenerational relations. We examined whether mentally simulated intergenerational contact (which is more easily facilitated and controllable) could reduce young adults' inclinations to avoid intergenerational interactions by increasing their inclusion of the older outgroup in the self (IOS), and by enhancing their stereotypes of older adults' warmth and competence. Method: We conducted an online experiment with 373 young adults from the United States. Participants imagined talking with an older adult (aged 70–75 years) in the circumstances intended to make salient either the older adult's warmth or their competence. Results: Both manipulations increased young adult participants' IOS with respect to older adults, which in turn predicted more positive assessments of older adults' warmth and competence. IOS, along with ratings of warmth and competence, inversely predicted the desire to avoid future interaction with older adults. Discussion: Findings indicate the viability of a simple and accessible intervention to improve intergenerational relations, which can be tailored to address different goals (e.g., encouraging intergenerational friendships vs. encouraging support for equal rights of older members of the workforce).